United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This Selected Issues paper summarizes estimates of the gap between current housing prices and their equilibrium levels in the United States. It examines short-term dynamics of price adjustment. Reflecting uncertainties about how to analyze underlying housing price trends, two approaches are used in the paper to estimate the extent of housing-price overvaluation. Both techniques yield similar results, revealing considerable overvaluation in the last few years, which has not been fully corrected yet. The gap between actual and equilibrium housing prices seems to matter only through its medium-term impact on the inventory-to-sales ratio.